Socialization of Household Organic Waste Processing Using the Takakura Composting Method as a Solution for Waste Management in Keru Village, Narmada, West Lombok - Baiq Fadila Arlina; Rachmawati Noviana Rahayu; Ernawati, Ernawati; Isrowati, Isrowati; Lalu Muhammad Aby Dujana; Julia Kartika (Future Tecno-Science Publisher, 2025)
Household waste management, especially organic waste, is still a serious problem that has not been resolved. So far, the people of Keru Village have not managed household waste independently and environmentally friendly, but rather disposed of it directly into the river or some of it was burned. The low participation of the Keru Village community in management is due to the low public awareness of the importance of proper waste management and the lack of community knowledge and skills related to simple and effective waste handling and management. This condition indicates the need for alternatives to reduce the volume of existing waste with environmentally friendly waste management through waste management training. The implementation of this activity consists of several stages, namely the initial preparation stage, the implementation stage consisting of delivering materials and demonstrations of composting and the evaluation stage with participatory discussions and Focus Group Discussions (FGD). The socialization activity was carried out well as indicated by the high enthusiasm of the socialization participants in asking questions and listening to the material and demonstrations of composting. The output of this activity is expected to increase the awareness, knowledge and skills of participants to process household organic waste into more useful products so that participants can start processing their household organic waste independently and can become drivers or pioneers of organic waste processing in their respective environments.